\( 4 x-3 y=-6 \) \( x-7 y=-14 \) solution
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the system of equations \( 4x - 3y = -6 \) and \( x - 7y = -14 \), you can use the substitution or elimination method. Let’s use the elimination method here. Multiply the second equation by 4 to align the coefficients of \(x\): 1. \(4(x - 7y) = 4(-14)\) gives you \(4x - 28y = -56\). Now, subtract the first equation from this new equation: \((4x - 28y) - (4x - 3y) = -56 - (-6)\) This simplifies to: \(-25y = -50\) So, divide both sides by -25 to find \(y\): \(y = 2\). Next, substitute \(y = 2\) back into one of the original equations to find \(x\): Using \(x - 7(2) = -14\): \(x - 14 = -14\) implies that \(x = 0\). Thus, the solution to the system is \( (0, 2) \). Now you’ve got the answer! 🎉